Designing Business Process Improvement that Concentrates on IT Utilization at LPPM UPN “Veteran” Jawa Timur - Mohamad Irwan Afandi; Eka Dyar Wahyuni (Nusantara Science and Technology Proceedings, 2020)
To enhance operational efficiency, several organizations have pursued business process re-engineering initiatives. Inevitably, this initiative involves the modernization and modification of existing information systems to support business processes. UPN "Veteran" Jawa Timur is no exception; as a higher education institution carrying out its tri-dharma mission, UPN needs to improve its efficiency continuously. Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) manages two of UPN "Veteran" Jawa Timur's tri-dharma related to research and community service. LPPM UPN Veteran itself is classified in an "independent" cluster so that independent research grants can be handled internally. This LPPM oversees the processes of administration and the execution of analysis and community service. There are many obstacles to implementing these processes at this time, such as data that is not recorded in a good structure, making it challenging when information is immediately required. And the most critical thing is that these data are still not integrated with performance data for lecturers. Therefore, this research aims to solve these problems by reviewing existing business processes and developing new business processes to improve current business processes. The result of this research is a list of functional and non-functional requirements of applications that will be developed.